Does the reason for discontinuation of a first TNF inhibitor influence the effectiveness of a second TNF inhibitor in axial spondyloarthritis? Results from the Swiss Clinical Quality Management Cohort. Issue 1 (December 2016) - Ciurea, Adrian; Exer, Pascale; Weber, Ulrich; Tamborrini, Giorgio; Steininger, Beate; Kissling, Rudolf; Bernhard, Jürg; Scherer, Almut
Abstract Background With regard to switching tumor necrosis factor inhibitors (TNFi) in axial spondyloarthritis (axSpA), conflicting results have been reported as to whether the effectiveness of a second TNFi depends on the reason for discontinuation of the first TNFi. Methods Patients with a clinical diagnosis of axSpA starting a second TNFi in the Swiss Clinical Quality Management cohort were included. Effectiveness of treatment at 1 year, as well as drug survival, was compared between subgroups having discontinued the first TNFi because of lack of response, adverse events (AEs), or other reasons. Lack of response was further divided into primary or secondary lack of response (PLR or SLR, respectively), depending on whether the first TNFi was stopped before or after 6 months of treatment. Results Among 632 patients with axSpA, median survival of a second TNFi was 1.1 years after PLR and 3.8 years after SLR (p = 0.003). At least moderate disease activity as defined by an Ankylosing Spondylitis Disease Activity Score using the erythrocyte sedimentation rate (ASDAS-ESR) <2.1 was achieved after 12 months by 11 %, 39 %, 26 %, and 39 % of patients who discontinued their first TNFi because of PLR, SLR, AEs, and other reasons, respectively (p = 0.01). Only 4 % of patients achieved an ASDAS-ESR inactive disease state after PLR, in comparison to 22 % of those after SLR. Similar results were demonstrated in patients fulfilling the Assessment of SpondyloArthritis international Society classification criteria for axSpA (n = 488): ASDAS-ESR <2.1 was achieved after 12 months by 9 %, 41 %, 29 %, and 39 % of patients who discontinued their first TNFi because of PLR, SLR, AEs, and other reasons, respectively (p = 0.01). Conclusions The effectiveness of a second TNFi is significantly impaired in patients with axSpA after PLR to a first TNFi compared with SLR.